2017
DOI: 10.1038/s41598-017-13468-z
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Emergence of Sparse Coding: A Dynamic Systems Approach

Abstract: During neocortical development, network activity undergoes a dramatic transition from largely synchronized, so-called cluster activity, to a relatively sparse pattern around the time of eye-opening in rodents. Biophysical mechanisms underlying this sparsification phenomenon remain poorly understood. Here, we present a dynamic systems modeling study of a developing neural network that provides the first mechanistic insights into sparsification. We find that the rest state of immature networks is strongly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(87 citation statements)
references
References 48 publications
(125 reference statements)
0
87
0
Order By: Relevance
“…This unstable FP, which disappears after the peak of the simGDPs, enables the emergence of simGDPs by building an amplification threshold (magenta line, Figure 5C) in the initial activity phase of the STP-RNN operating at its rest state. The simGDPs can be effectively triggered only if the perturbation is sufficiently strong enough to push activity of the STP-RNN beyond the amplification threshold ( Figure 5C) (Rahmati et al, 2017). This underlies a relatively all-or-none characteristic of simGDPs, which is a wellknown property of experimentally measured GDPs.…”
Section: Som Ins Can Synchronize Ca1 Network Activity In An Nkcc1-depmentioning
confidence: 86%
See 2 more Smart Citations
“…This unstable FP, which disappears after the peak of the simGDPs, enables the emergence of simGDPs by building an amplification threshold (magenta line, Figure 5C) in the initial activity phase of the STP-RNN operating at its rest state. The simGDPs can be effectively triggered only if the perturbation is sufficiently strong enough to push activity of the STP-RNN beyond the amplification threshold ( Figure 5C) (Rahmati et al, 2017). This underlies a relatively all-or-none characteristic of simGDPs, which is a wellknown property of experimentally measured GDPs.…”
Section: Som Ins Can Synchronize Ca1 Network Activity In An Nkcc1-depmentioning
confidence: 86%
“…To investigate the mechanism of simGDP emergence, we plotted the A s À A p -plane of the network with slow STP dynamics frozen at the rest state (Frozen STP-RNN; Figure 5C; STAR Methods). We found that an unstable fixed point (FP; black dots in A s ; Figures 5C and 5E) is hidden in the network's fast dynamics, which does not exist in the non-frozen STP-RNN (Rahmati et al, 2017). This unstable FP, which disappears after the peak of the simGDPs, enables the emergence of simGDPs by building an amplification threshold (magenta line, Figure 5C) in the initial activity phase of the STP-RNN operating at its rest state.…”
Section: Som Ins Can Synchronize Ca1 Network Activity In An Nkcc1-depmentioning
confidence: 94%
See 1 more Smart Citation
“…However, during neocortical development, the activity of developing neural networks transitions from this highly synchronized mode (with a synchronization level of about 80%) to a relatively sparse mode after the postnatal onset of sensory transduction [44,[87][88][89]. While this so-called sparsification phenomenon is thought to refine sensory coding [58], our findings may provide some additional mechanistic explanation for the actual purpose of sparsification. That is, our resutls ( Figure 7C) suggest that the neuronal communication in immature cortices lacking sensory inputs (e.g., in mice visual cortex during first postnatal week [43,44,90]) may not be reliably energy efficient.…”
Section: Implications Of Neuronal Synchronization For Energy Efficmentioning
confidence: 65%
“…the portion of neurons participating in the synchronous event) can be modulated by e.g., the features of the external stimulus (e.g. orientation, intensity level, or context), switching attention [40,45,[55][56][57], or the internal state of the network [58]. Nonetheless, to model the synaptic activity with a controlled synchronization level we use a simple procedure for generating spikes and synchronous patterns.…”
Section: Modeling Presynaptic Inputsmentioning
confidence: 99%